The Inflammatory Bowel Disease Knowledge Inventory Device 2 (IBD-KID2) is an effective tool for measuring disease-specific knowledge in Chinese patients - HaiQun Huang; Ping Li; Angharad Vernon-Roberts; Andrew S. Day; BaiLing Liu; ZhaoRu Wu; Yuling Liu; QiaoRu Ye; He Wang (PLoS ONE, 2025)
Background The Inflammatory Bowel Disease Knowledge Inventory Device 2 (IBD-KID2) is a specialized tool designed to evaluate disease-specific knowledge in patients with inflammatory bowel disease. The aim of this study was to develop a Chinese version of IBD-KID2 and to test the reliability and validity of this tool in Chinese patients with IBD. Methods A Chinese version of IBD-KID2 was developed through initial cultural relevance/comprehension review and adaptation using content validity index for individual items (I-CVI, level > 0.78 acceptable) and the scale overall (S-CVI, level > 0.8 acceptable). A standardized approach was used to translate IBD-KID2 to Chinese, with the final tool being 15 items long and scored as one point for each correct answer (maximum score of 15). Tool validity was evaluated in a convenience sample of patients with IBD. External reliability was evaluated using test-retest analysis in a participant subset two weeks after baseline completion and internal reliability evaluated using cohort scores (Cronbach’s alpha, Cronbach’s α). Results Following expert review for cultural relevance/comprehension the original IBD-KID2 scored > 0.78 I-CVI and > 0.9 for the S-CVI, and the tool was then translated. Ninety-six participants with IBD completed the Chinese IBD-KID2; 68 (71%) were male, eight (8%) aged < 18 years, and 63 (66%) had Crohn’s disease. The mean IBD-KID2 score of the cohort was 9.2 (±3.2, range 3-14). Scores decreased with age (p = 0.012) and increased with higher levels of education (p < 0.001). The retest reliability in a subset of 30 patients showed a correlation of 0.89 (P < 0.001), with no difference between the two time points (mean difference 0.4, = 0.16). The tool had high internal consistency with a Cronbach’s α coefficient of 0.8. Conclusion The Chinese version of the IBD-KID2 demonstrated satisfactory reliability and validity, making it a robust instrument for evaluating disease-specific knowledge in individuals with IBD.